2018
DOI: 10.1111/age.12703
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of deleterious mutations in the domestic yak genome

Abstract: Deleterious mutations play an important functional role, affecting trait phenotypes in ways that decrease the fitness of organisms. Estimating the frequency of occurrence and abundance has been a topic of much interest, especially in crops and livestock. The processes of domestication and breeding allow deleterious mutations to persist at high frequency, and identifying such deleterious mutations is particularly important for breed improvement. Here, we assessed genome-wide patterns of deleterious variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 52 publications
6
23
0
Order By: Relevance
“…This is due to the role of genetic drift that elevates the frequency of SNVs due to bottleneck, inbreeding and artificial selection. Previous studies on dog breeds and yaks showed a higher number of homozygous deleterious SNVs in domesticated canines or yaks than those present in their respective wild relatives [6,15]. Since homozygous SNVs represents high frequency variants, our results are in consensus with those reported by the above-mentioned studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is due to the role of genetic drift that elevates the frequency of SNVs due to bottleneck, inbreeding and artificial selection. Previous studies on dog breeds and yaks showed a higher number of homozygous deleterious SNVs in domesticated canines or yaks than those present in their respective wild relatives [6,15]. Since homozygous SNVs represents high frequency variants, our results are in consensus with those reported by the above-mentioned studies.…”
Section: Discussionsupporting
confidence: 92%
“…This was confirmed by a previous study that compared the exomes of dog breeds and wild wolves and found a higher proportion of homozygous deleterious SNVs in dogs than wolves [6]. Similarly, domesticated yak populations were reported to have higher number of homozygous deleterious amino acid changing SNVs than those estimated for wild yaks [15]. High frequency deleterious variants causing diseases such as retinal degeneration in European cattle breeds has been attributed to the process of domestication and artificial selection [16].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…2015; Xie et al . 2018). Several of these genes are related to smell perception and chemical stimuli (Hu 2012).…”
Section: Domestication Dispersal and Differentiation Of Breedsmentioning
confidence: 99%
“…With the development of modern biotechnology, increasing numbers of researchers are conducting molecular biology research pertaining to the environmental adaptability of this mammal. In the last few years, high-throughput studies on yaks, such as genome and miRNA sequencing and transcriptome analysis, have become popular 13 15 . In fact, there are still many unexplored areas of basic research in this animal.…”
Section: Introductionmentioning
confidence: 99%